Micro Injection Molding - Tosello, Guido, author 648562; ScienceDirect (Online service) 7722 (Cincinnati : Hanser, 2018)
This book deals exclusively with micro injection molding and overcoming the challenges of managing and processing polymer materials at ultra-small scales. Micro injection molding is the primary process for the mass production of polymer components with critical dimensions in the sub-millimeter range; however, it is not just a simple downscaling of conventional injection molding, and specific material-process-product interactions must be understood in order to achieve near zero-defect net-shape micro molded products. Micro molding is typically associated with ultra-high accuracy and superior process capabilities. Micro molded products have dimensional tolerances down to the single-digit micrometer range and surface finish with roughness from the sub-micrometer down to a few nanometers range. Micro and nano-structured tool surfaces are reproduced with very high replication fidelity onto the polymer products. Micro injection molding is highly suitable for the manufacture of multifunctional micro components such as micro implants, microfluidic systems, polymer micro optical elements, and micro mechanical systems. This book provides engineers, project managers, researchers, consultants, and other professionals involved in precision polymer processing and micro manufacturing with a comprehensive, up-to-date, and detailed treatment of the main topics related to micro molding, from material and process technology to tooling, to key-enabling technologies, and multimaterial process variations.